Phyto-sociological Studies of a Traditional Reserve forest - Thal Ke Dhar, Pithoragarh, Central Himalayas (India) - Negi, Chandra S.; Nautiyal, Sunil (Indian Forester, 2005)
Traditional reserve forests or sacred forests have in the recent years attracted the attention of conservation scientists as well as that of wildlife officials, for the reason that they are the last vestiges of forests which were once in their prime. They are the last remnants of the biodiversity and are zealously guarded by the common village folks, wbo safeguard these patches of greens, through their own sets of rules, in the form of taboos, religious sanctions and belief systems. Forests being no longer in possession of the villagers, sanction mechanisms have denigrated with the passage of time, as the villagers no longer perceive these forests as belonging to them. However, inspite of the ordeal of the times, there are still few sacred forests, wherein these mechanisms are still enforced. Sacred forest of ’ThaI Ke Dhar’ is one such forest. Phytosociological study in ThaI Ke Dhar sacred forest has been carried out in view to understand the structure, regeneration potential and conservation status.